Preference and Use Pattern of Electronic Books among Postgraduate Students in a Nigerian University - Oladokun, Bolaji David; Tom-George, Nnenda W.; Abdulrahman, Abdulrazaq Baba; Idoniboye-Obu, Tamunotonye Ibimina; Maxwell, Charity Ezinne (Journal of Digital Learning and Education, 2024)
This study investigated the preferences and use patterns of e-books among postgraduate students at Prince Abubakar Audu University. Four (4) research objectives guided the conduct of this study. A descriptive survey method was used for the study and a questionnaire was used for data collection. Statistical tools used for this analysis were frequency counts, simple percentages, and mean scores. The study concludes that eBooks are highly valued by postgraduate students, due to their ability to enhance productivity and effective learning. The ease of use and clear graphical illustrations further contribute to the preference for eBooks, making them indispensable tools in the academic pursuits of postgraduate students. The study highlights that eBooks are extensively utilized for a variety of academic purposes, including coursework completion, research, exam preparation, assignments, and reference needs. Despite the evident benefits, the study reveals varying levels of satisfaction among students, with a significant portion using eBooks only to some extent. Several challenges impede the optimal use of eBooks, such as high costs, device-related inefficiencies, limited access to computers or the internet, readability issues, and the need for operational skills. The study recommended that university libraries should expand their eBook collections and seek partnerships with publishers to provide more affordable or even free access to essential academic texts and universities should consider initiatives to provide or subsidize devices optimized for reading eBooks, such as tablets or e-readers with suitable screen sizes.